Challenge and Prospect of Traditional Chinese Medicine in Depression Treatment - Zhang, Yuan-Wei; Cheng, Yung-Chi (Frontiers in Neuroscience, 2019)
Current medication for depression is inadequate and far from ideal. Development of novel antidepressant drugs is a pressing task. The discovery of ketamine and related agents represents a new era in drug discovery for the rapid treatment of depression. Due to potential neurotoxicity, short-lasting efficacy, the limitation of a single target approach, and a limited role in depression prevention of these agents, additional approaches or drugs that exert synergy and compatibility, with the rapid-acting agents are required for better treatment of depression. Traditional Chinese Medicine (TCM) is a systems medicine and its clinical experience and integrated theory for diagnosis and treatment provides an alternative method of novel drug discovery in depression treatment. In TCM, there are numerous claimed effective antidepressant formulas, but comprehensive research and evidence-based clinical studies are required for their acceptance as a treatment. In this essay, we review current attempts in the discovery of new agents, TCM drug formulation, and TCM treatment of depression, and discuss the challenges and opportunities of TCM in the new era of antidepressant discovery. TCM could provide an important resource in the discovery of novel agents, assistance of the rapid-acting antidepressants, development of new agents for female patients, and the prevention of depression at its early stages. The study of depression in conjunction with TCM therefore not only provides an opportunity to scientifically evaluate the benefits and risks of TCM, but also accelerates the development of novel antidepressant agents by combining the principle of modern molecular medicine with the ideas of empirical systems medicine.